Impact of Fiscal Policy on Inequality and Poverty in the Arab Republic of Egypt - Lara Ibarra, Gabriel (World Bank, Washington, DC, 2019)
This study assesses the redistributive impact of fiscal policy –– including expenditures and taxation –– in the Arab Republic of Egypt. Using a broadly applied methodology, a fiscal incidence analysis is conducted using survey and government data for fiscal year 2015. Evidence shows that Egyptian fiscal policy reduces income inequality, and that among individual fiscal programs, the largest reduction is due to public expenditures on the primary education system. Compared with similar countries, Egypt's overall fiscal policy placed it in the median of the distribution of inequality reduction. Fiscal policies in Egypt also led to a decrease in poverty, mostly from the flagship Tamween program. Poverty and inequality could be reduced more effectively if the country would shift away from spending on untargeted energy subsidies to more targeted transfers. The large gap between the government's expenditures and revenues helps explain the positive outcomes on poverty and inequality but poses challenges in the long term.